Biochemical Markers in The Vaginal Washing and Insulin-Like Growth Factor Binding Protein in The Diagnosis of Membrane Rupture - Erdemoğlu, Evrim; Güney, Mehmet; Mungan, Tamer (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: The aim of this study was to evaluate the diagnostic significance of IGFBP-1 applied by a dipstick method in comparison with nitrazine test and AFP/creatinine/HCG in the vaginal fluid. STUDY DESING: Thirty-six women with definite premature rupture of membranes (PROM) and 35 women without PROM were included in the study. Speculum examination, nitrazine test and IGFBP-1 detection by a rapid strip test and the analyses of AFP, HCG, and creatinine were performed. RESULTS: Sensitivity of IGFBP-1 test and nitrazine test was estimated to be 97%. Cut-off values for AFP (21 IU/l), creatinine (0.24 mg/dl) and HCG (702 mIU/ml) were determined by ROC analysis. Regression analysis revealed IGFBP-1 (p<0.01) as the most accurate test. Combination of AFP and creatinine was beneficial in discriminating membrane rupture (p<0.01). Likelihood ratios of PROM test, AFP, and combined AFP-creatinine tests were all of the same order of magnitude (≈34,≈0,05) and likely to be clinically important but not significantly different from each other in their clinical performance. CONCLUSION: IGFBP-1, AFP and combination of AFP-creatinine are accurate tests, holding immense importance with regard to clinical performance.